1990
DOI: 10.1210/endo-126-4-1873
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Regulation of the Hypothalamo-Pituitary Adrenal Axis in the Genetically Obesefa/faRat*

Abstract: Adrenalectomy has been shown to reverse most facets of the syndrome of the genetically obese fa/fa rat. However, a detailed analysis of the hypothalamo-pituitary-adrenal (HPA) axis in these animals is lacking. In the present study, morning corticosteronemia was higher in obese rats of both sexes than in lean ones, whereas evening corticosteronemia was higher only in obese male rats. The HPA axis was further investigated using stressful stimuli. Immobilization, ether, and cold stresses resulted in greater corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 26 publications
4
81
1
1
Order By: Relevance
“…As expected, CRF 1 receptor blockade attenuated the activity of the HPA axis. Three weeks of treatment with SSR125543 reduced the basal plasma corticosterone levels in lean rats and prevented the fastinginduced corticosterone response in obese Zucker rats, which are hypercorticosteronemic (Guillaume-Gentil et al 1990, Richard et al 1996 and hypersensitive to stress (GuillaumeGentil et al 1990, Timofeeva & Richard 1997. Similarly, a previous study showed that SSR125543 reduced the basal adrenocorticotropic hormone (ACTH) concentrations and attenuated the CRF-and stress-induced increase in circulating ACTH in Sprague-Dawley rats .…”
Section: Discussionmentioning
confidence: 96%
“…As expected, CRF 1 receptor blockade attenuated the activity of the HPA axis. Three weeks of treatment with SSR125543 reduced the basal plasma corticosterone levels in lean rats and prevented the fastinginduced corticosterone response in obese Zucker rats, which are hypercorticosteronemic (Guillaume-Gentil et al 1990, Richard et al 1996 and hypersensitive to stress (GuillaumeGentil et al 1990, Timofeeva & Richard 1997. Similarly, a previous study showed that SSR125543 reduced the basal adrenocorticotropic hormone (ACTH) concentrations and attenuated the CRF-and stress-induced increase in circulating ACTH in Sprague-Dawley rats .…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, the administration of GC in the neonatal period produces in adults a decrease in the expression of GC receptors in several areas of the brain, and this could explain the disruption of feedback mechanisms (34). High levels of plasma corticosterone and/or ACTH are found in other models of obesity in rodents (35,36), and in humans, the HPA seems to contribute to the metabolic syndrome (37). Moreover, cortisol is elevated in patients with type 1 and diabetes, and in many of them, GC administration Values are mean Ïź SEM of at least three cages, each containing three animals (cumulative daily food intake).…”
Section: Discussionmentioning
confidence: 99%
“…The altered activity of the hypothalamic NPY system in these rats results, not only from insensitivity to insulin (53) and mutations of the leptin receptor (4), but also from increased plasma corticosterone concentrations (56) and increased sensitivity to corticosterone (57). In turn, NPY increases, via a positive feedback, plasma corticosterone concentrations (32).…”
Section: Involvement Of Complex Interactions Between the Hpa Axis Andmentioning
confidence: 99%